(untitled) (Tabanque. Revista Pedagógica, 2018)
One of the most popular functions of word processors is to cut and paste. This paper studies this activity, with a special focus on its usefulness and its impact on punctuation marks. We will see the need for changes in sentence for certain effects: closeness, distance and style (we illustrate it with examples from the current press). We also present an exercise model for this technique that can be stimulating and especially helpful to familiarize students and editors with the composition of the sentence and the mobility of its components.